PENGARUH PANDEMIC COVID-19 DAN PASAR SAHAM ASEAN TERHADAP PASAR SAHAM INDONESIA - Jul Fahmi Salim (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2022)
This study examines the effect of the number of COVID-19 cases and the price of shares in ASEAN countries on the stock market in Indonesia. The ARDL model is used in research in order to see the long-term and short-term effects. The results of the analysis show that in the long term only the Malaysian stock market has a significant effect on the Indonesian stock market, besides that in the short term it is found that the Malaysian stock market, Singapore stock market and the number of Covid cases in Malaysia have a significant effect on the Indonesian stock market.